Anti-colon cancer activity of Bifidobacterium metabolites on colon cancer cell line SW742 - Bahmani, Sepideh; Azarpira, Negar; Moazamian, Elham (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Bacteria species, which are used as probiotics, are lactic acid bacteria. The majority of them are under the genera Bifidobacterium and Lactobacillus. The aim of the present study was to isolate and identify Bifidobacterium and to evaluate the effects of their 24 h and 120 h cell-free supernatants (CFS) from both cultures on colon cancer cell line. Materials and Methods: In the present study, 84 samples of dairy products, infant feces, and probiotic capsule were collected, and Bifidobacterium was isolated. Gram stain, biochemical tests, and molecular identification were done for the isolation and identification of Bifidobacterium. Cytotoxicity effects of CFS derived from both cultures of isolated Bifidobacterium were assessed on colon cancer cell lines. Results: In the present study, 17 isolates of Bifidobacterium were identified. The results show that Bifidobacterium was most frequently associated with infant feces and dairy products, whereas the lowest rate was associated with local milk. After the effects of CFS on colon cancer cell line, two isolates were identified from infant feces and probiotic capsule; they had the highest ability in inhibiting the growth of cancer cells. Bifidobacterium bifidum was effective in combating cancer cells and was associated with a substantial improvement in gastrointestinal cancer. Conclusion: The study has shown that the regular ingested probiotics could prevent the development of colorectal cancer. During the present study, the produced CFS could inhibit the growth of colon cancer cells. In conclusion, probiotics have good potential to be introduced as a new approach to colon cancer treatment.